Healing and Mortality Rates Following Toe Amputation in Type 2 Diabetes Mellitus - Vassallo, Ian Mario; Gatt, Alfred; Cassar, Kevin; Papanas, Nikolaos; Formosa, Cynthia (Experimental and Clinical Endocrinology & Diabetes, 2019)
Background and Aim This single-centre study aimed to determine healing, re-ulceration, re-amputation and mortality rates at one year after toe amputations in patients with type 2 diabetes (T2DM).Patients and Methods Eighty-one participants with T2DM admitted for toe amputation were included. Patient characteristics, peripheral circulation and neuropathy status were recorded. Subjects were then followed every 3 months post-amputation for a year.Results Overall, 59.3% of participants underwent further surgery (n=31 to revise the original amputation site and n=17 to amputate a new site). During 12 months, 45.7% of participants presented with a new ulcer at a different site. Mortality was 7.4%. In 12.4% of participants, the amputation site remained incompletely healed. Only 20.9% had no complications in 12 months. At 12 months, 80.2% of study cohort had a completely healed amputation site.ConclusionIn conclusion, this study highlighted high re-intervention, re-amputation and new ulceration rates. Strategies to improves these outcomes in such high-risk patients are warranted.
Keywords: diabetic foot; mortality; foot morbidity; amputations; healing